Leadership Philosophy and Its Implications for the Climate of Educational Organizations - Rinto, Petrus; Wicaksono, Luhur; Ali, Moh. (JUPE : Jurnal Pendidikan Mandala, 2024)
This article discusses the philosophy of leadership and its implications for organizational climate in the educational context. Leadership philosophy refers to the principles, values and beliefs that form the basis for making decisions and acting as a leader. In the educational sphere, an effective leadership philosophy can form a positive organizational climate, which in turn has an impact on performance. and motivation of organizational members. This research explores various leadership theories and models, and examines how the application of certain leadership philosophies can influence aspects of organizational climate such as communication, collaboration, and psychological well-being. The study results show that leadership based on inclusive, collaborative values and oriented towards shared goals tends to create an environment that supports professional and personal growth. This article concludes that a deep understanding of leadership philosophy and its consistent application is very important to create a conducive and productive educational organizational climate.